2020
DOI: 10.1002/fsn3.1342
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin improves preeclampsia‐induced cell apoptosis by regulation of TLR4/NF‐κB in rats

Abstract: To explain gastrodin improved cell apoptosis induced by preeclampsia in vivo and in vitro study. The PE and normal rats were injected with normal saline (Model), low‐dose gastrodin (Gas‐L), medium‐dose gastrodin (Gas‐M), and high‐dose gastrodin (Gas‐H) groups at 50, 100, or 200 mg/kg per day. The rat blood pressure and 24‐hr urine protein level were measured at pregnant days 10, 16, and 20. Evaluating pathology by H&E staining, the cell apoptosis by TUNEL, and MyD88 and NF‐κB (p65) proteins by IHC assay using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Placenta inflammation is known to result from TLR4 signaling partially. It has been reported that the activation of the TLR4/NF‐κB pathway has a strong correlation with the development of PE 36 . The activated placental TLR4/NF‐kB pathway, which subsequently induces the secretion of downstream inflammatory cytokines and chemokines, 35 may be another intermediary factor in the cascade reaction of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Placenta inflammation is known to result from TLR4 signaling partially. It has been reported that the activation of the TLR4/NF‐κB pathway has a strong correlation with the development of PE 36 . The activated placental TLR4/NF‐kB pathway, which subsequently induces the secretion of downstream inflammatory cytokines and chemokines, 35 may be another intermediary factor in the cascade reaction of PE.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the crucial function of the activated immune system characterized by an imbalance between anti‐inflammatory and proinflammatory factors in the pathogenesis of PE has been discovered 23 . Substantial evidence has shown that the accelerated apoptosis of trophoblasts and retardant intrauterine growth can be caused by imbalanced concentrations of pro‐ and anti‐inflammatory cytokines in the PE placenta 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, injection of SC-39100 reversed these effects (Figure 5E-H According to previous studies, the crucial function of the activated immune system characterized by an imbalance between anti-inflammatory and proinflammatory factors in the pathogenesis of PE has been discovered. 23 Substantial evidence has shown that the accelerated apoptosis of trophoblasts and retardant intrauterine growth can be caused by imbalanced concentrations of pro-and antiinflammatory cytokines in the PE placenta. 24 TNFα, IL-6, and IFN-γ are pivotal proinflammatory cytokines and mediators in the immune system of pregnant women and are overproduced by immune cells of PE patients.…”
Section: Pae Attenuates Placental Inflammation By Inhibiting the Jak2...mentioning
confidence: 99%
“…This study also confirmed that VEGF can induce the proliferation, migration and tube formation of HUVECs. Besides, from previous studies, it was found that gastrodin can suppress the apoptosis induced by preeclampsia by regulating the TLR4/NF-κB of HTR/SVneo cells [ 19 ]. Liu et al found that gastrodin antagonized the up-regulation of stress signals from the endoplasmic reticulum by activating the Nrf2 pathway, including the expression of GRP78, CHOP, and phosphorylated eIF2α, reducing osteoporosis in rats caused by glucocorticoids [ 20 ].…”
Section: Discussionmentioning
confidence: 99%